2016
DOI: 10.1051/0004-6361/201629168
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 183 GHz H2O megamaser emission towards NGC 4945

Abstract: Aims. The aim of this work is to search Seyfert 2 galaxy NGC 4945, a well-known 22 GHz water megamaser galaxy, for H 2 O (mega)maser emission at 183 GHz. Methods. We used APEX SEPIA Band 5 (an ALMA Band 5 receiver on the APEX telescope) to perform the observations. Results. We detected 183 GHz H 2 O maser emission towards NGC 4945 with a peak flux density of ∼3 Jy near the galactic systemic velocity. The emission spans a velocity range of several hundred km s −1 . We estimate an isotropic luminosity of >1000 L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Ellingsen et al (2014) observe offsets of 180 and 300 pc for the northeast and southwest components, respectively. Although the H 2 O maser emission observed in NGC 4945 is not physically associated with the 36.2 GHz maser emission, the redshifted components share an overlapping velocity range (Greenhill et al 1997;Hagiwara et al 2016;Humphreys et al 2016;Pesce et al 2016).…”
Section: Properties Of Methanol Maser Environmentmentioning
confidence: 87%
“…Ellingsen et al (2014) observe offsets of 180 and 300 pc for the northeast and southwest components, respectively. Although the H 2 O maser emission observed in NGC 4945 is not physically associated with the 36.2 GHz maser emission, the redshifted components share an overlapping velocity range (Greenhill et al 1997;Hagiwara et al 2016;Humphreys et al 2016;Pesce et al 2016).…”
Section: Properties Of Methanol Maser Environmentmentioning
confidence: 87%
“…In extragalactic sources, the 22 GHz line is most commonly used to search for maser emission – more than 150 sources have been found to emit water maser emission, mostly in galaxies with active galactic nuclei (AGN, e.g., Lo 2005; Pesce et al 2016). The 183 GHz line has been detected towards NGC 3079 (Humphreys et al 2005), Arp 220 (Cernicharo et al 2006b; Galametz et al 2016), and most recently towards NGC 4945 (Humphreys et al 2016). In both NGC 3079 and NGC 4945, the 183 GHz maser emission is associated with the AGN.…”
Section: Introductionmentioning
confidence: 99%
“…No maser emission is detected in the second epoch (2016 November) as the strength of the maser has decreased below the detection limit (3 σ) of 38 mJy. Also, a counterpart to the highly redshifted velocity feature at V LSR = 1138.6 km s −1 in the 183 GHz H 2 O maser spectrum (Humphreys et al 2016) was not found in the second epoch spectrum. In the Circinus galaxy, the most prominent H 2 O maser emission is detected with a peak flux density of 1.56 Jy at V LSR = 601.6 km s −1 with a signal-to-noise ratio (SNR) of >80 and a 1 σ rms level of ∼19 mJy per spectral channel (Figure 3).…”
Section: Tidbinbilla Observationsmentioning
confidence: 90%
“…H 2 O maser emission occurs at (sub-)millimeter wavelengths in external galaxies: the pioneering observational study of extragalactic (sub-)millimeter masers was the discovery of H 2 O maser in the 3 13 − 2 20 transition (ν rest = 183.31009 GHz) toward the LINER galaxy NGC 3079 (Humphreys et al 2005), which was later fol-lowed by the detection of a 183 GHz maser in the nearby AGN NGC 4945 (Humphreys et al 2016). Hagiwara et al (2013) conducted a search for H 2 O masers in the 10 29 −9 36 transition (ν rest = 321.226 GHz) toward H 2 O megamaser galaxies, which resulted in the first extragalactic detection of a 321 GHz H 2 O maser toward the center of the Circinus galaxy, obtained with the Atacama Large Millimeter/submillimeter Array (ALMA).…”
Section: Introductionmentioning
confidence: 99%